Growing into Work - Pseudo Panel Data Evidence on Labor Market Entrance in Germany - Joachim Inkmann; Stefan Klotz; Winfried Pohlmeier (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1998)
The German apprenticeship training system is generally acknowledged to solve the youth unemployment problem prevalent in many European countries by providing on-the-job training that often leads into subsequent regular employment within the training firms. Little attention has been paid to those youths who either fail their apprenticeship training or do not find a job afterwards. Both events may not only be associated with a depreciation of human capital but also may serve as a screening device for potential employers. In this paper we try to analyze empirically if a failed labor market entrance reduces subsequent earnings and if a potential reduction lasts over the individual's labor market history. We construct a pseudo panel of birth cohorts for a sample of West German males born between 1930 and 1965 from three repeated cross sections observed in 1979, 1985/86, and 1991/92. Analyzing the pseudo panel data we find a strong negative impact on earnings for both a failed apprenticeship training and a failed transition into regular employment. While the latter effect lasts over the individual's labor market history the former effect is compensated with increasing labor market experience.
Keywords: J24; J31; C23; 330; Apprenticeship Training; Labor Market Entrance; Earnings; Cohorts; Pseudo Panel Estimation